The Effect of Financial Performance, Company Size, And Operational Cash Flow on Earnings Per Share With GCG as a Moderating Variable - Masfufah, Maratul; Hidayat, Rendra Arief (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to determine the effect of return on asset, debt to equity, total asset turnover, firm size, and operating cash flow on earnings per share with good corporate governance as a moderating variable in property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. This research employs a quantitative approach using secondary data obtained from the official IDX website. The total sample consists of 96 observations selected through purposive sampling. Data analysis was conducted using IBM SPSS 25 software, with multiple linear regression and Moderated Regression Analysis (MRA) models applied to test the hypotheses. The results show that Return on Assets, Debt to Equity, Total Asset Turnover, firm size, and operating cash flow have a positive effect on Earnings per Share. Furthermore, Good Corporate Governance, measured by managerial ownership, is proven to simultaneously moderate the relationship between financial performance, firm size, and operating cash flow on Earnings per Share. These findings indicate that financial performance and company characteristics play a crucial role in determining EPS. Managerial ownership, as one of the mechanisms of good corporate governance, serves as a supporting factor in optimizing the influence of financial performance, firm size, and operating cash flow on earnings per share.